2015
DOI: 10.3238/arztebl.2015.0496
|View full text |Cite
|
Sign up to set email alerts
|

Place of Death

Abstract: Most people in Germany die in institutions; the most common place of death is still the hospital, where more than half of all deaths take place. Only one death in four occurs at home. There is a marked secular trend away from dying at home or in the hospital, in favor of dying in a care or nursing home; death in palliative care units and hospices is also becoming more common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
24

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 24 publications
4
45
0
24
Order By: Relevance
“…The palliative care needs were developed by the research based on literature reviews consisting of 13 items. It asks about different of needs: information (item 1-3), physical (item 4-7), emotional/spiritual (items 8-10) and social supports (item [11][12][13]. Each item represents one need of cancer patients and scale was rated on a scale from 1 (not importance) to 5 (very importance).…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The palliative care needs were developed by the research based on literature reviews consisting of 13 items. It asks about different of needs: information (item 1-3), physical (item 4-7), emotional/spiritual (items 8-10) and social supports (item [11][12][13]. Each item represents one need of cancer patients and scale was rated on a scale from 1 (not importance) to 5 (very importance).…”
Section: Measurementmentioning
confidence: 99%
“…The ultimate goal is to provide patients and families with the best QOL during the trajectory of diseases [11]. The data from previous studies showed that many terminally ill patients would prefer to stay and die in their own homes, but unfortunately some of patients may not be able to do so [11][12][13][14]. Evidence has presented many benefits of home care for palliative care patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patient preferences for home as the place of care, at 37-63%, were surprisingly lower than expected in comparison with preferences for the hospital, at 28-53%, which were higher than assumed. However, these results confirm the tendency of a broadly acknowledged higher preference for a home death [3][4][5][6]. A systematic review of the United Kingdom literature highlighted a contrasting view of patient preferences, concluding that patients' preferred POD is unknown because of large amounts of missing data and the handling of these missing data.…”
Section: Preferences For the Place Of Carementioning
confidence: 53%
“…The data from previous studies showed that many terminally ill patients would prefer to stay and die in their own homes, but unfortunately, some patients may not be able to do so. [1][2][3][4][5][6] Even though there are many factors associated with successful home deaths (ie, the patient's or family's preference, the patient's performance status during the last days, the patient's awareness of the disease status and prognosis), receiving palliative home visits from the multidisciplinary care teams is one of the key factors that enable patients to die at home. [7][8][9][10][11] Previous evidence has supported many benefits of home care for palliative care patients.…”
Section: Introductionmentioning
confidence: 99%